Structural, luminescence and electrical conductivity of strontium titanate thin films prepared by dip coating method - Maarof, Saleha (2014)
Strontium titanate (SrTiO3) sol-gel was deposited onto glass substrates by dip coating method. The effects of deposition parameters such as different annealing temperatures and number of coating layers were studied. Strontium nitrate anhydrous (Sr(NO3)2), titanium isopropoxide (C12H28O4Ti), ethylene glycol (HOCH2CH2OH) and nitric acid (HNO3) were used to prepare sol-gel of strontium titanate. Ethylene glycol was added to promote polymerization between C12H28O4Ti and Sr(NO3)2. The samples structure were characterized by X-ray diffraction (XRD), atomic force microscopy (AFM), Fourier transform infra red (FT-IR) and photoluminescence (PL) spectroscopy. XRD analysis showed the process of the intermediate crystalline phase of Sr(NO3)2 with lattice parameter a = b = c = 0.78 nm for as-prepared sample. An amorphous inorganic phase was found for samples annealed at 300 and 400 °C. The samples began to change to SrTiO3 phase after being annealed at 500 °C with lattice parameter a = b = c = 0.39 nm and peak orientation at planes (110), (111), (200) and (211). Thin films with double coating layers showed clearer peaks orientation. The microstructure study using AFM revealed the grain size in the range 220 – 460 nm and surface roughness in the range 33 – 69 nm at 500 ºC for different number of coating layers. FT-IR analysis shows that SrTiO3 crystallization phase was completely formed at higher temperatures of 500, 600 and 700 ºC. PL spectroscopy of SrTiO3 thin films appeared to have spectra emission in the region of 310 - 510 nm wavelength. The spectra also showed the different peaks appearing at different annealed temperatures. Van der Pauw technique was used to measure the electrical conductivity and activation energy for single and four coating layers samples at 500 ºC annealing temperature. The results showed that the electrical conductivity for single layer was higher than the four coating layers. Activation energy in high temperature region were in the range of 0.656 meV and 0.446 meV whereas activation energy in low temperature region were in the range of 0.162 meV and 0.105 meV for single and four coating layers samples, respectively